Implementasi Kurikulum Merdeka dalam Pembentukan Karakter di SD 060870 Medan Sebagai Sekolah Penggerak - Hotma Tiolina Siregar; Septia Dwinanda Girsang; Mei Shelya Delloya Br Sembiring; Lidia Loviga Br Barus; Chelsy Simanungkalit (Civiliza Publishing, Indonesia., 2025)
Character education is an important part of developing students who are moral, independent, responsible, and able to face the challenges of modern development. The implementation of the Independent Curriculum at SD Negeri 060870 Medan as a Driving School is not only carried out through classroom learning activities, but is also integrated into various extracurricular activities and school development programs that support the strengthening of student character. This study aims to describe the implementation of the Independent Curriculum in character formation at SD Negeri 060870 Medan. The internship program begins with an orientation activity that provides students with an understanding of the school environment, organizational structure, work culture, and programs implemented at the school. During the internship, students participate in learning activities and various school programs, thus gaining real-life experience in developing competencies as future educators. The results of the study indicate that the implementation of the internship program provides benefits for both students and the school, and supports the implementation of the Independent Curriculum through various innovative programs, such as literacy visits, reforestation, arts and creative activities, and anti-bullying programs. These programs are able to create a more conducive learning environment, increase student participation, and strengthen character values ​​that are in line with the dimensions of the Pancasila Student Profile.